Comparative Analysis of ‘Children Who Break the Law’ Development Program in Indonesia and Malaysia - Ridha Husnul Hayati; Rila Rahma Mulyani; Zahratul Azizah; Anggi Firmanjaya Saputra (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2023)
This article aims to compare legal child development programs in Indonesia and Malaysia, the meaning and ages of children, and the basic principles of child protection law in Indonesia and Malaysia. The method used is a comparative study of the legal systems for child protection between Indonesia and Malaysia, as well as the method of analyzing the contents of different references to the topics discussed. There are many similarities when comparing the legal systems for child protection in Indonesia and Malaysia; two legal systems protecting children in each country. Special protection such as care, education, care and adoption, religion and abandoned children and care, rehabilitation, care for children, child protection, investigation, and care or exploitation of children, economically, sexually, educationally, or at school, as well as providing special protection against beatings, disability, and child abuse. The difference is that the protection law in Malaysia has been incorporated into the Child Protection Act 2001 (Tapu 611), whereas in Indonesia it remains separate from the Child Protection Act.